The basal ganglia, the ideal machinery for the cost-benefit analysis of action plans - Hwang, Eun Jung (Frontiers in Neural Circuits, 2013)
Basal ganglia dysfunction causes profound movement disorders, often attributed to imbalance between direct and indirect pathway activity in the sensorimotor basal ganglia. In the classical view, the direct pathway facilitates movements, whereas the indirect pathway inhibits movements. However, the recent finding of co-activation of the two pathways during movement challenges this view. Reconciling the new finding with the body of evidence supporting the classical view, this perspective proposes that the direct pathway computes the expected benefits of motor plans entering the basal ganglia, while the indirect pathway computes their expected costs. Thus, basal ganglia output combining the two pathway signals in a subtractive manner weighs benefits against costs, and endorses the plan with the best prospective outcome via feedback projections to the cortex. The cost-benefit model, while retaining the antagonistic roles of the two pathways for movements, requires co-activation of the two pathways during movement as both benefit and cost are computed for every movement. The cost-benefit model, though simple, accounts for a number of confounding results, and generates new focus for future research with testable predictions.